Exploring elements: Playfulness as an ally in teaching the Periodic Table - Lobo, Thainar Lopes; Vieira, Tainara Campos; Negrão, Charles Alberto Brito; Rodrigues, Waleria Magno; Martins , Vitória Caroline de Souza; Lima, João Pedro dos Reis; Araújo, Marcos William Leão de; Pantoja, Samantha Siqueira; Souza, Silvia Helena da Silva e; Souza, Ewerton Carvalho de; Silva, Antonio dos Santos (Seven Editora, 2024)
Chemistry teaching is often seen as difficult and unattractive to students, mainly because it deals with many abstract concepts that are worked through traditional teaching methodologies that do not place students as subjects of their learning. This work explores the potential transformation of the learning environment and increasing the quality of education by incorporating playfulness, through educational games and interactive simulations in the teaching of Chemistry, especially the Periodic Table. The approach promotes practical and contextualized understanding, connecting abstract concepts to everyday situations and makes learning enjoyable. This pedagogical change contributes to training students with a scientific and curious mindset. This work presents the game entitled "Elementar: War of the Atomic Clans", which is a card game inspired by RPG, designed to familiarize students with chemical elements using the Periodic Table. The careful elaboration of the letters, using low-cost materials and computational resources, highlights the importance of creativity and interdisciplinary collaboration in education, contributing to a more solid and meaningful education. DOI:https://doi.org/10.56238/sevened2024.009-013